Product Differentiation Strategy for Organizational Financial Profitability: Enchancing Market Share and Profitability- A Comprehensive Literature Review - Tojiri, Yusuf (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This research aims to explore the impact of product differentiation strategies on a firm's competitive advantage and market performance and organizational financial profitability, particularly within highly competitive markets. The study is anchored in the resource-based view (RBV) and the positioning perspective, providing a theoretical lens through which the multifaceted nature of differentiation is examined. Methodologically, this investigation synthesizes a comprehensive literature review with empirical data, utilizing quantitative methods to assess the correlation between differentiation strategies and their effectiveness in enhancing market share and profitability. The findings reveal that effective product differentiation, encompassing unique product attributes, innovative technologies, and a well-orchestrated marketing mix, significantly contributes to a firm's competitive edge. Specifically, the integration of advanced technologies like artificial intelligence and the Internet of Things into product offerings not only enhances functional attributes but also elevates the customer experience, thereby distinguishing products in saturated markets. Additionally, strategic brand management and the alignment of marketing mix components are crucial in communicating value and building brand equity, which in turn supports sustained competitive advantage. These results underscore the critical role of dynamic capabilities in adapting product strategies to evolving market conditions and consumer preferences, highlighting the necessity for firms to continually innovate and tailor their offerings to maintain market relevance and leadership.